Community Service to Develop Businesses in the 'Tuah Negri' Enterprise to Enhance National Competitiveness in Collaboration with the Ministry of Cooperatives and SMEs - Hidayat, Danny (Andalasian International Journal of Social and Entrepreneurial Development, 2023)
The community service project at "Tuah Negri" aims to enhance national competitiveness through collaboration with the Ministry of Cooperatives and SMEs. It focuses on improving operational efficiency, expanding markets, and adopting technology. The project designs strategies to enhance the well-being of small and medium-sized enterprises at the local level through needs identification, training programs, and coaching. We integrate technology, strengthen operational management, and enhance marketing. The evaluation indicates positive achievements, yet challenges in financial management and optimization of financial structure require further attention. Collaboration with the Ministry of Cooperatives and SMEs brings strategic benefits, and monitoring provides a foundation for continuous adjustment and learning. In conclusion, this project contributes to the development of local businesses and establishes a foundation for sustainable strategy development. These challenges become the focal point for future considerations, with additional efforts in understanding and improving financial management. The project establishes a strong basis for closer partnerships and plans for disseminating results and best practices through seminars and workshops. With these measures, the project is expected to deliver a sustainable positive impact and inspire similar initiatives in various regions